Lead time reduction in SME by using value stream mapping (VSM) technique - Farah Liyana, Hassan (2013)
This research is related to a study on lead time reduction in SME by using value stream mapping (VSM) technique. VSM was pioneered in the 1980s by Toyota’s chief engineer, Taiichi Ohno and sensei Shigeo Shingo. VSM is the tool or technique to identify the non-value added activities by eliminating it in order to improve the productivity of the company. The objectives of this study are to improve the production lead time, eliminate non- value added at the selected production line or model and lastly to propose a new production system. This study was conducted at Zest Venture (Kadlawo), Kuantan. The systematic approach on methodologies was applied as to ensure the study is successfully carried out. The techniques used were visual observation, survey and time study. The study was taken place for every two weeks. All collected information was illustrated in the VSM chart for further analysis on non-value added activities. The study shows few activities were considered non valued added such as paper stacking at the finishing rack after the printing process and long waiting time after printing and cutting process. Therefore, a few suggestions were proposed to the company’s owner for further action. The implemented improvement had proven the process flow become more efficient and smoothly run without interruption. As a result, the product lead time also reduced from 94.3 minutes to 66 minutes. In term of financial benefits, the company could save about RM1800.60 per month.